A Multistage Decision-Feedback Receiver Design for LTE Uplink in Mobile Time-Variant Environments - Juinn-Horng Deng; Shu-Min Liao (International Journal of Antennas and Propagation)
Single-carrier-frequency division multiple access (SC-FDMA) has recently become the preferred uplink transmission scheme in long-term evolution (LTE) systems. Similar to orthogonal frequency division multiple access (OFDMA), SC-FDMA is highly sensitive to frequency offsets caused by oscillator inaccuracies and Doppler spread, which lead to intercarrier interference (ICI). This work proposes a multistage decision-feedback structure to mitigate the ICI effect and enhance system performance in time-variant environments. Based on the block-type pilot arrangement of the LTE uplink type 1 frame structure, the time-domain least squares (TDLS) method and polynomial-based curve-fitting algorithm are employed for channel estimation. Instead of using a conventional equalizer, this work uses a group frequency-domain equalizer (GFDE) to reduce computational complexity. Furthermore, this work utilizes a dual iterative structure of group parallel interference cancellation (GPIC) and frequency-domain group parallel interference cancellation (FPIC) to mitigate the ICI effect. Finally, to optimize system performance, this work applies a novel error-correction scheme. Simulation results demonstrate the bit error rate (BER) performance is markedly superior to that of the conventional full-size receiver based on minimum mean square error (MMSE). This structure performs well and is a flexible choice in mobile environments using the SC-FDMA scheme.